In honor of Fadime: murder and shame - Wikan, Unni (University of Chicago Press, 2008)
Fadime, in remembrance -- Sara: "too Swedish" for a right to live -- Pela, or history repeats itself -- What is honor? -- The cross-cultural context of honor killing -- Virginity, virility, and honor -- At a trial -- Little sister, thirteen years old -- A mother's story -- Naive or primitive? -- Strength born from grief -- Intermission : honor in the courtroom -- Nadia's case : another question of honor --The Zedini case : was honor at stake? -- The Lörenskog murder : rethinking honor -- The man in the woods -- The mother -- Speaking in parliament -- Integration -- At stake : a perception of humanity -- Longing for a family